miRNAs: Potential as Biomarkers and Therapeutic Targets for Cancer - Al-hassan, Ahmed; Rezvani, Zahra (Journal of Biomedicine and Biochemistry, 2024)
Background MicroRNAs (miRNAs) are pivotal regulators of gene ex-pression, playing a significant role in various human and canine disorders.Dysregulation of miRNA expression is a hallmark of most malignancies.Objective This review aims to analyze the importance of miRNAs in cancer research, focusing on their potential as diagnostic and prognostic biomarkers. Additionally, the study explores the therapeutic possibilities of miRNA-based therapies and the role of miRNAs in revealing mechanisms of resistance to conventional chemotherapy.Results The study underscores the diverse roles of miRNAs in cancer research. miRNAs hold promise as diagnostic and prognostic indicators,offering significant clinical insights. Furthermore, miRNA-based therapies show potential in. improving patient outcomes by providing tailored ap- proaches to cancer treatment. Understanding miRNA production and reg-ulation in cancer can elucidate mechanisms of chemotherapy resistance, paving the way for more effective cancer therapies.Conclusion miRNAs hold immense promise for revolutionizing cancer management through liquid biopsies. Their ability to facilitate early detec-tion, monitor disease progression, and guide personalized therapies offers a powerful tool in the fight against cancer. As research progresses, we can anticipate a future where liquid biopsies powered by miRNAs become a cornerstone of effective cancer care, leading to improved patient outcomes and a brighter future for cancer management.